2019
DOI: 10.1007/s40617-019-00363-4
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Peers to Support Academic Learning for Children With Autism Spectrum Disorder

Abstract: The inclusion of students with autism spectrum disorder in academic settings is becoming more common. However, most practices focus on increasing social skills even though students also struggle in academic areas. There is a need for strategies that address both social and academic skill deficits, are evidence based, and are easy to implement in the classroom. Peermediated interventions have evidence supporting their use in promoting social and academic behavior change and are socially valid and cost-effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…Hass et al suggested that peer-assisted learning strategies, peer-mediated instruction, and class-wide peer tutoring effectively support academic learning skills in children with autism. 44 Plavnick and Hume indicated that the incorporation of observational learning in intervention programmes with strategies such as live modelling, video modelling, and group and dyadic instruction are effective for teaching various skills to children with autism. 45 These findings can help in the development of effective intervention programmes for individuals with autism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hass et al suggested that peer-assisted learning strategies, peer-mediated instruction, and class-wide peer tutoring effectively support academic learning skills in children with autism. 44 Plavnick and Hume indicated that the incorporation of observational learning in intervention programmes with strategies such as live modelling, video modelling, and group and dyadic instruction are effective for teaching various skills to children with autism. 45 These findings can help in the development of effective intervention programmes for individuals with autism.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, multiple studies have reported that diverse intervention programmes can improve the academic and social performance of children with autism. Hass et al suggested that peer‐assisted learning strategies, peer‐mediated instruction, and class‐wide peer tutoring effectively support academic learning skills in children with autism 44 . Plavnick and Hume indicated that the incorporation of observational learning in intervention programmes with strategies such as live modelling, video modelling, and group and dyadic instruction are effective for teaching various skills to children with autism 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Cooperative learning is one of the PMIs with efficacy for building relationship skills for students with EBD (Mitchell et al, 2003). PMIs are a research-based practice that have demonstrated positive effects across a number of academic and social variables (Dunn et al, 2017; Haas et al, 2019; Herpratiwi et al, 2018). PMIs are strategies that create opportunities for peers to promote social behaviors for all students, including children with disabilities (Haas et al, 2019; Ryan et al, 2008).…”
Section: Cooperative Learningmentioning
confidence: 99%
“…PMIs are a research-based practice that have demonstrated positive effects across a number of academic and social variables (Dunn et al, 2017; Haas et al, 2019; Herpratiwi et al, 2018). PMIs are strategies that create opportunities for peers to promote social behaviors for all students, including children with disabilities (Haas et al, 2019; Ryan et al, 2008). Some examples include peer modeling, peer monitoring, peer network strategies, peer tutoring, classwide peer tutoring (CWPT), peer-assisted learning strategies (PALS), classwide student tutoring teams, peer mentoring, and cooperative learning (Dunn et al, 2017; Ryan et al, 2004).…”
Section: Cooperative Learningmentioning
confidence: 99%
“…Estas experiencias se han desarrollado fundamentalmente en aulas no universitarias (Gardiner e Iarocci, 2014), siendo uno de los recursos educativos (Programas de Instrucción mediados por pares) más efectivos (Zeneli y Tymms, 2015). Existen algunas experiencias universitarias para estudiantes con grandes necesidades apoyo (Carter et al et al, 2005) y experiencias específicas para estudiantes universitarios con TEA (Haas et al et al, 2019) en las que se intenta extrapolar las experiencias no universitarias. En general, reconociendo las bondades de la instrucción mediada por pares, las dificultades de encontrar estudiantes universitarios en la misma aula hacen difícil la sistematización de este tipo de apoyo.…”
Section: Programas De Mentores Y De Pares Voluntariosunclassified